Bionic Fishtail-Shaped Proprioceptive Sensing Technology Based on Triboelectric Nanogenerator - Liu, Bo; Xu, Peng; Xu, Xiaoyan; Liu, Jianhua; Guo, Linan; Li, Yuanzheng; Guan, Tangzhen; Xu, Minyi (Chinese Automation Congress (Online), 2023)
Accurate motion posture prediction is crucial for bionic robot fish (BRF) to fulfill military strategies and perform efficient underwater detection. Inspired by the proprioceptive sensing ability of caudal fins, we propose a prototype of tri-boelectric nanogenerators fish-tail-shaped proprioceptive sensing (FPSP) to assist BRF in predicting its self-motion posture. The FPSP consists of a flexible tail fin-like shell and three triboelectric nanogenerator sensing units, which are able to convert the bending of the flexible shell into a voltage output. The motion posture of BRF can be predicted by analyzing the voltage output of FPSP in a complex flow field environment. Experimental results have demonstrated the promising potential of proprioceptive sensors in augmenting the control capabilities of BRF.